Odpowiedzi

2010-02-24T19:00:46+01:00
(x+5y)-(4+2x)-3y-1)=x+5y-4-2x-3y-1=x+2y-5
(2a(kwadratowe)+a-1)-(2-2a-3a(kwadratowe)+(a-a(kwadratowe-3)=2a(k)+a-1-2+2a+3a(k)+a-a(k)-3=5a(k)+6a-1
(kwadratowe=k)
2010-02-24T19:04:06+01:00
(x+5y)-(4+2x)-3y-1)= x+5y-(-12y-4-6xy-2x)=x+5y+12y+4+6xy+2x=3x+17y+4+6xy

(2a(kwadratowe)+a-1)-(2-2a-3a(kwadratowe)+(a-a(kwadratowe-3)= 2a(kwadratowe)+a-1-2+2a+3a(kwadratowe)-a+a(kwadratowe)+3= 6a(kwadrat)+3a

-2(2-5x)+(1-4x)= -4+10x+1-4x=6x-3

6a-(2a-3b)+(a-6b)= 6a-2a+3b+a-6b=5a-3b

Jeśli gdzieś się pomyliłam to sorki xD, ale chyba jest dobrze.